As narrativas de professoras reencantadas pela educação ambiental : rede de formação tecida no/com o cotidiano - Ferreira, Nadja Valéria dos Santos (2012)
The objective of this research is to understand the constitution of an instituting movement of teachers from a public school located in Xerém district, Duque de Caxias (RJ), which points what can be defined as self-collective and continuous, emerged into the principles of Environmental Education. The procedural form as it stands has the distinction of bringing an Environmental Education emancipatory potential, anchored in solidarity, in the dialog and in the collective action, triggered by an educational practice and policy, in the Youth and Adult Education, which focuses on inter and transdisciplinarity approaches. The focus of this research was the production of adult education teacher’s narrative, and the outstanding identity processes of the practitioners in the district of Xerém. Collective action to seek refuge in culture and is reflected in the complexity of the idea of an Ecology of Knowledge that reflects the environment they live and live the various subjects. The methodology chosen was guided by cartography to tell the stories of practicing teachers with their students from the production of data that allowed rediscover invisible knowledge translated into social and environmental practices